Pemetaan Potensi Nagari Dan Pengembangan Web GIS Nagari Indudur Berbasis Partisipatif - Muhammad Fahrur Rozi; Vikhi Marionas Saputra; Milla Hanifa; Shinta Wahyuni; M. Eric Laksmana Awidani; M. Ikram Prananta Bangun (CV. ITTC INDONESIA, 2026)
Village potential mapping is a strategic effort to support data-driven local development planning. Nagari Indudur in Solok Regency, West Sumatra, possesses diverse natural and cultural resources that remain undocumented. This community service activity aimed to map village potentials and develop a participatory Web GIS platform. Methods included field observation, participatory GPS mapping, spatial data processing, and open-source Web GIS development. Results showed a comprehensive potential map covering agriculture, agroforestry, socio-cultural assets, and ecotourism, integrated into an accessible Web GIS platform. Participatory mapping combined with Web GIS improves data accuracy, transparency, and supports sustainable village development planning.